2021
DOI: 10.3389/fcell.2021.651449
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Interactions of the Peroxisomal Proteins PEX5 and PEX14

Abstract: Human PEX5 and PEX14 are essential components of the peroxisomal translocon, which mediates import of cargo enzymes into peroxisomes. PEX5 is a soluble receptor for cargo enzymes comprised of an N-terminal intrinsically disordered domain (NTD) and a C-terminal tetratricopeptide (TPR) domain, which recognizes peroxisomal targeting signal 1 (PTS1) peptide motif in cargo proteins. The PEX5 NTD harbors multiple WF peptide motifs (WxxxF/Y or related motifs) that are recognized by a small globular domain in the NTD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Most matrix proteins use a C-terminal peroxisometargeting signal (PTS1) that is defined by the consensus sequence [S/A/C] [K/R/H] [L/H] and is sufficient to artificially target cytosolic proteins to the peroxisome [55,56]. PTS1 proteins are recognized by the soluble cytosolic receptor Pex5, which contains a Cterminal PTS1-binding domain and an intrinsically disordered N-terminal domain [57][58][59][60][61] (Figure 1B). Some cargo proteins lacking a PTS1 tag bind Pex5's N-terminal domain; for these proteins, the N-terminal half of Pex5 is sufficient for import [62][63][64].…”
Section: Matrix Protein Importmentioning
confidence: 99%
See 1 more Smart Citation
“…Most matrix proteins use a C-terminal peroxisometargeting signal (PTS1) that is defined by the consensus sequence [S/A/C] [K/R/H] [L/H] and is sufficient to artificially target cytosolic proteins to the peroxisome [55,56]. PTS1 proteins are recognized by the soluble cytosolic receptor Pex5, which contains a Cterminal PTS1-binding domain and an intrinsically disordered N-terminal domain [57][58][59][60][61] (Figure 1B). Some cargo proteins lacking a PTS1 tag bind Pex5's N-terminal domain; for these proteins, the N-terminal half of Pex5 is sufficient for import [62][63][64].…”
Section: Matrix Protein Importmentioning
confidence: 99%
“…Although the membrane topology of Pex13 and Pex14 has been controversial [68,[78][79][80], recent evidence suggests that Pex13's N-terminus and Pex14's C-terminus are in the peroxisome lumen, and the opposite termini are cytosolic [81,82]. Multiple copies of Pex5 oligomerize in the pore and these are thought to be integral structural components of the DTM [65], although the nature and relevance of any direct contacts between Pex5 and the lipid bilayer are unclear [61,67,83]. Pex proteins involved in Pex5 export-Pex8, Pex2, Pex10, Pex12, Pex15, Pex1, and Pex6-are also associated with the DTM [84].…”
Section: Matrix Protein Importmentioning
confidence: 99%
“…The N-terminal region additionally includes four predicted amphipathic helices (designated AH1-AH4 in Fig. 3A) of unknown significance (Gaussmann et al, 2021). AH1 resides downstream of Cys11 and has a hydrophobic surface conserved across eukaryotes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PEX5 cycles between a cytosolic and membrane-associated state and interacts with the PMP PEX14 to deliver matrix proteins to the peroxisome for their import across the membrane. Using NMR, it was recently demonstrated that the disordered N-terminal domain of human PEX5 weakly interacts with membrane-mimicking lipid bicelles, which stabilises transient amphipathic helices in this region of the protein (Gaussmann et al, 2021). Similarly, the globular N-terminal domain of human PEX14 was also shown to interact weakly with peroxisome-like lipid bilayers, although this did not lead to any overall structural changes and was independent of its transmembrane domain.…”
Section: Pex-lipid Interactions Regulating Peroxisome Biogenesismentioning
confidence: 99%
“…Similarly, the globular N-terminal domain of human PEX14 was also shown to interact weakly with peroxisome-like lipid bilayers, although this did not lead to any overall structural changes and was independent of its transmembrane domain. The association of PEX5 with the membrane does not significantly alter its binding affinity for PEX14 and the interaction of PEX14 with the membrane is readily outcompeted by its binding to PEX5, which occurs at partially overlapping sites (Gaussmann et al, 2021). Together, this suggests a possible model whereby the PEX14-phospholipid interaction partially hides the PEX5 binding site, preventing low-affinity non-specific interactions with other cytosolic proteins in the absence of PEX5, but being easily displaced when PEX5 is present to permit docking.…”
Section: Pex-lipid Interactions Regulating Peroxisome Biogenesismentioning
confidence: 99%